Identification of RUNX1T1 as a potential epigenetic modifier in small‐cell lung cancer - Tian He; Gary Wildey; Karen McColl; Alyssa Savadelis; Kyle Spainhower; Cassidy McColl; Adam Kresak; Aik Choon Tan; Michael Yang; Ata Abbas; Afshin Dowlati (Molecular Oncology, 2021)
Small‐cell lung cancer (SCLC) can be subgrouped into common ‘pure’ and rare ‘combined’ SCLC (c‐SCLC). c‐SCLC features a mixed tumor histology of both SCLC and non–small‐cell lung cancer (NSCLC). We performed targeted exome sequencing on 90 patients with SCLC, including two with c‐SCLC, and discovered RUNX1T1 amplification specific to small cell tumors of both patients with c‐SCLC, but in only 2 of 88 ‘pure’ SCLC patients. RUNX1T1 was first identified in the fusion transcript AML1/ETO, which occurs in 12%‐15% of acute myelogenous leukemia (AML). We further show higher expression of RUNX1T1 in the SCLC component of another c‐SCLC tumor by in situ hybridization. RUNX1T1 expression was enriched in SCLC compared with all other cancers, including NSCLC, in both cell lines and tumor specimens, as shown by mRNA level and western blotting. Transcriptomic analysis of hallmark genes decreased by stable RUNX1T1 overexpression revealed a significant change in E2F targets. Validation experiments in multiple lung cancer cell lines showed that RUNX1T1 overexpression consistently decreased CDKN1A (p21) expression and increased E2F transcriptional activity, which is commonly altered in SCLC. Chromatin immunoprecipitation (ChIP) in these overexpressing cells demonstrated that RUNX1T1 interacts with the CDKN1A (p21) promoter region, which displayed parallel reductions in histone 3 acetylation. Furthermore, reduced p21 expression could be dramatically restored by HDAC inhibition using Trichostatin A. Reanalysis of ChIP‐seq data in Kasumi‐1 AML cells showed that knockdown of the RUNX1T1 fusion protein was associated with increased global acetylation, including the CDKN1A (p21) promoter. Thus, our study identifies RUNX1T1 as a biomarker and potential epigenetic regulator of SCLC.